Biodegradation Life of Science - Chamy, Rolando; Rosenkranz, Francisca (IntechOpen, 2013)
This book contains a collection of different biodegradation research activities where biological processes take place. The book has two main sections: A) Polymers and Surfactants Biodegradation and B) Biodegradation: Microbial Behaviour.